Audit Committee and Firm Characteristics on Audit Report Lag: Moderated by Key Audit Matters - Pradistyo, Shafa April; Suryandari, Dhini (Dinasti Publisher, 2026)
The purpose of this study is to assess the moderating role of the primary audit issue in energy sector businesses and to investigate the impact of audit committee size, frequency of audit committee meetings, company size, and leverage on audit report lag. Purposive sampling strategies were used to collect secondary data from the Indonesia Stock Exchange for the years 2023 to 2025 utilizing a causal quantitative methodology. Panel data regression analysis with a fixed effects model was applied as the main testing method. The research results prove that the size and meetings of the audit committee do not affect reporting delays. On the contrary, the size of the company has been proven to accelerate the release of reports, while a high level of debt significantly prolongs the audit completion time. Furthermore, the main audit issue did not prove to moderate the influence of audit committee or firm characteristics on audit duration. In conclusion, the timeliness of financial information release is highly dependent on the scale of assets and the entity's debt risk, where the complexity of auditor findings has become a standard procedure that no longer disrupts the reporting timeline.